Comparison of Economically Important Loci in Landraces and Improved Wheat Cultivars from Pakistan. Issue 1 (1st January 2016) - Rasheed, Awais; Xia, Xianchun; Mahmood, Tariq; Quraishi, Umar Masood; Aziz, Abdul; Bux, Hadi; Mahmood, Zahid; Mirza, Javed Iqbal; Mujeeb‐Kazi, Abdul; He, Zhonghu
ABSTRACT: We investigated alleles at 31 loci associated with adaptability, yield, and end‐use quality in 107 wheat ( Triticum aestivum L.) landraces (WLRs) and 121 improved historical wheat cultivars (HWCs) from Pakistan. The WLRs were categorized into two further subgroups: 36 pre‐Green‐Revolution landraces released as cultivars and 71 geographically spread landraces from all over Pakistan. Alleles Vrn‐A1a, TaGW2‐6A‐A, TaCKX6‐D1b, Pinb‐D1b, Psy‐A1b, and Wx‐D1b were absent in WLRs, whereas ample diversity was observed at all other loci. In HWCs, only Wx‐D1b and Glu‐A3e were absent among the alleles tested, whereas the alleles Ppd‐D1a (90%), Rht‐B1b or Rht‐D1b (83.4%), TaCwi‐A1a (95%), TaGW2‐6A‐G (76%), TaCKX6‐D1a (77.3%), Glu‐A1b (66.1%), Glu‐D1d (61.3%), Pina‐D1b (88.2%), Pinb‐D1a (90%), Psy‐A1a (66.1%), Psy‐B1b (81.8%), Psy‐D1a (86.5%), Ppo‐A1a (70%), TaZds‐D1b (73.9%), TaLox‐B1b (80.1%), and Wx‐D1a (100%) predominated, indicating significant improvement in adaptability, yield potential, and end‐use quality and unconscious selection for favored alleles. Higher frequencies of favored alleles at the TaCwi‐A1 and TaCKX6‐D1 loci influencing 1000‐kernel weight (TKW) in HWCs indicated that selection pressure on these alleles during breeding successfully contributed to cultivar improvement. Wright's pairwise fixation index (Fst) statistics indicated greater genetic divergence between HWC and WLR collections (0.16) than HWC and WLR cultivars (0.14). Population structure based on functional markers (FMs) using principal component analysis partitioned the germplasm into two distinct groups. High genetic divergence and low admixture between HWCs and WLRs indicated limited use of landraces in wheat breeding in Pakistan. Our results suggested these collections as rich reservoirs of alleles and haplotype combinations that may be useful in future breeding programs.